Adoption, development and learning process (Journal of Parents and Teachers, 2012)
The author of this article explains that children that have problems of development are in this situation because they didn’t experience the necessary conditions at the adequate time so that they could develop properly.  In this article are explained the different reasons why children can end up suffering these problems and how school should help solving this situations.
Keywords: Adoption; problems of development; learning process.